The pricing of voting rights in Finland : A study on dual-class shares - Tuuri, Sami (My University, 2025)
This thesis examines the determinants of the voting premium in Finnish dual-class shares. The voting premium refers to the price difference between superior and inferior voting shares, often reflecting the value of control. The study utilizes daily, monthly, and quarterly data from nine Finnish listed companies between 2005 and 2024, focusing on liquidity, ownership structure, and financial leverage as explanatory factors. The empirical analysis is conducted using unbalanced random effects panel regression, which accounts for firm-specific heterogeneity while preserving variation across time. The results show that liquidity significantly influences the voting premium. Higher relative trading volume of superior voting shares increases the premium, while a larger relative bid-ask spread reduces it. Ownership structure also proves to be an important determinant. Both strategic and institutional ownership are positively related to the voting premium, suggesting that private benefits of control remain relevant in Finland despite strong minority protection. In addition, financial leverage is found to have a positive relationship with the voting premium, supporting the hypothesis that leverage helps controlling shareholders maintain influence with less capital investment. The results are robust across alternative model specifications and consistent with some previous findings, while also revealing market-specific characteristics of the Finnish dual-class share market. This thesis contributes to the existing literature by providing updated evidence on the pricing of voting rights in Finland and highlights the continued relevance of ownership structure and liquidity in explaining voting premiums.

Tämä tutkielma tarkastelee äänestyspreemion määräytymistä suomalaisissa eri osakesarjoja käyttävissä yhtiöissä. Äänestyspreemiolla tarkoitetaan osakkeiden välistä hintaeroa, jossa paremmilla äänioikeuksilla varustetut osakkeet ovat yleensä kalliimpia, mikä usein heijastaa kontrollin arvoa. Tutkimus hyödyntää päivittäistä, kuukausittaista ja neljännesvuosittaista aineistoa yhdeksästä suomalaisesta pörssiyhtiöstä vuosilta 2005–2024. Selittävinä tekijöinä tarkastellaan likviditeettiä, omistusrakennetta ja rahoitusrakennetta. Empiirinen analyysi toteutetaan epätasapainotetulla satunnaisvaikutteiden paneeliregressiolla, joka huomioi yhtiökohtaisen heterogeenisyyden säilyttäen samalla ajallisen vaihtelun. Tulokset osoittavat, että likviditeetillä on merkittävä vaikutus äänestyspreemioon. Paremmilla äänioikeuksilla varustettujen osakkeiden suhteellisesti suurempi kaupankäyntivolyymi kasvattaa preemiota, kun taas suurempi suhteellinen osto- ja myyntihinnan välinen erotus alentaa sitä. Myös omistusrakenne on keskeinen tekijä: sekä strateginen että institutionaalinen omistus ovat yhteydessä korkeampaan preemioon, mikä viittaa siihen, että yksityiset kontrolliedut ovat edelleen relevantteja Suomessa, huolimatta vahvasta vähemmistösuojasta. Lisäksi rahoitusvipuvaikutuksella havaitaan olevan positiivinen yhteys äänioikeuspreemioon, mikä tukee hypoteesia, jonka mukaan velka mahdollistaa määräysvallan säilyttämisen pienemmällä oman pääoman sijoituksella. Tulokset ovat johdonmukaisia eri mallispesifikaatioiden välillä ja vastaavat osin aiempia havaintoja, mutta paljastavat myös Suomen osakemarkkinalle ominaisia piirteitä. Tämä tutkielma täydentää aiempaa kirjallisuutta tarjoamalla päivitettyä empiiristä näyttöä äänioikeuksien hinnoittelusta Suomessa ja korostaa omistusrakenteen ja likviditeetin merkitystä äänestyspreemion selittämisessä.
Keywords: Voting premium, Dual-class shares, Control benefits, Liquidity, Finnish stock market, Äänestyspreemio, Osakesarjat, Määräysvallan hyödyt, Likviditeetti, Suomen osakemarkkinat